2014
DOI: 10.4172/1948-5948.s8-006
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Antiviral Activity and GC-MS Analysis of Essential Oil Extracted from Achillea fragrantissima Plant Growing In Sinai Peninsula, Egypt

Abstract: Medicinal plants are considered new resources for producing agents that could act as alternatives to antibiotics in treatment of antibiotic-resistant bacteria. The present study aimed to evaluate the efficacy of essential oil extracted from Achillea fragrantissima plant growing in Egypt for antimicrobial, antiviral activities and chemical composition analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). We also performed determination of essential oil antimicrobial activity by agar desk diffusion method an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
(53 reference statements)
1
15
0
Order By: Relevance
“…7), from all this component, the number and percentage of sesquiterpenes component were four compounds; methyl 3,4-tetradecadienoate, betacubebene, beta-selinene, and benzofuran, 7-cyclohexyl-2,3-dihydro-2-methyl-which represented 7.01% from all compounds in essential oil, and monoterpenes were 35 compounds (61.40%). Our results agree with other literatures, monoterpenes are the principal components of Achillea essential oils (Zeedan, et al, 2014;Mottaghi, et al, 2016). Furthermore, 1, 8-cineole (20.1%), camphor (15.6%), and viridiflorol (11.8%) the three most abundant monoterpene components (Toker, et al, 2003).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…7), from all this component, the number and percentage of sesquiterpenes component were four compounds; methyl 3,4-tetradecadienoate, betacubebene, beta-selinene, and benzofuran, 7-cyclohexyl-2,3-dihydro-2-methyl-which represented 7.01% from all compounds in essential oil, and monoterpenes were 35 compounds (61.40%). Our results agree with other literatures, monoterpenes are the principal components of Achillea essential oils (Zeedan, et al, 2014;Mottaghi, et al, 2016). Furthermore, 1, 8-cineole (20.1%), camphor (15.6%), and viridiflorol (11.8%) the three most abundant monoterpene components (Toker, et al, 2003).…”
Section: Resultssupporting
confidence: 94%
“…Most researchers reported that santolina alcohol, artemisia ketone, cis-thujone, and trans-thujone were the major constituents in A. fragrantissima (Shalaby and Ricchter, 1964;El-Deeb, 1985;Hifnawy, et al, 2001;El-Shazly, et al, 2004;Abaas, et al, 2013;and Alsohaili and Al-fawwaz, 2014). In addition, borneol and 1,8-cineole (Gohari, et al, 2011;Mazandarani, et al, 2013;Zeedan, et al, 2014). However, our results vary in the chemical composition of essential oils of A. fragrantissima, as well as the number and ratio of chemical components.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…In addition, moderate activity was observed for B. subtilis, S. aureus, Sarcina lutea, and E. coli with inhibitory zones ranging from 20 to 25 mm [36]. Similarly, Achillea fragrantissima essential oil was effective against S. aureus , S. epidermidis , and E. coli with the highest inhibition zone of 26 mm, 16 mm, and 16 mm, respectively [19]. In a study by Radaelli et al [127], a major food-borne disease-causing agent, C. perfringens , was inhibited by essential oils of Brazilian MAPs such as basil, rosemary, marjoram, peppermint, thyme, and Pimpinella anisum (anise).…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 99%
“…Roy et al [100] indicated the potential antiviral activity of Trachyspermum ammi oil against Japanese encephalitis virus (JEV). Similarly, Zeedan et al [19] reported the antiviral activity of Achillea fragrantissima against the ORF virus (a parapox virus). More recently, Pourghanbari et al [145] evaluated in vitro antiviral activity of M. officinalis (lemon balm) essential oil and oseltamivir and their synergistic effect on avian influenza virus (AIV) subtype H9N2.…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 99%